PENGARUH LATIHAN PASSING BAWAH BERPASANGAN TERHADAP KETERAMPILAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWI YANG MENGIKUTI EKSTRAKURIKULER DI SMK NEGERI 1 PANGKALAN LESUNG - Asep Riadi; Aref Vai; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The aim of this study is to find out the effectsof paired bump pass training on bump pass skill in volleyball for The female students Who took on extracurricular activities at SMA Negeri 1 pangkalan lesung. This study was conducted by applying an experimental method with